Job Vacancy Chains and Local Employment Creation; the Case of Supply-Side Restrictions - Daniel Felsenstein; Joseph Persky (European Regional Science Association (ERSA), 2006)
The job-chains model of local labor market change is a demand-driven analytic device for estimating the effects of new job creation. This paper explores the effects of restricting supply, i.e. limiting job access, on the model's primary outcomes: vacancy chain multipliers, welfare effects and distributional impacts. Major sources of labor supply are the local unemployed, out of the labor force and in-migrants. Three simulations are reported relating to 1) restricting new jobs to current local residents (i.e. no in-migrants), 2) restricting new jobs to current residents in the first round of hiring only and 3) restricting hiring to local unemployed/out of labor force on the first round alone. The results are compared to the basic model that assumes no supply-side restrictions. In terms of chain length, welfare effects, distributional impacts and policy palatability, first round restrictions on in-migrants would seem to be the most plausible option. However, as an economic development strategy,well targeted demand-side initiatives would still seem to be preferable.
Keywords: 330